2006
DOI: 10.1038/sj.bjc.6603392
|View full text |Cite
|
Sign up to set email alerts
|

Reduced BRCA1 expression due to promoter hypermethylation in therapy-related acute myeloid leukaemia

Abstract: BRCA1 plays a pivotal role in the repair of DNA damage, especially following chemotherapy and ionising radiation. We were interested in the regulation of BRCA1 expression in acute myeloid leukaemia (AML), in particular in therapy-related forms (t-AML). Using real-time PCR and Western blot, we found that BRCA1 mRNA was expressed at barely detectable levels by normal peripheral blood granulocytes, monocytes and lymphocytes, whereas control BM-mononuclear cells and selected CD34 þ progenitor cells displayed signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 16 publications
2
52
0
Order By: Relevance
“…Apart from the above polymorphisms, several studies implicate BRCA1 (involved in initial recognition of a double strand break) and BRCA2 gene (involved in Homologous Recombination) deficiencies in AML pathogenesis. Scardocci et al observed that 32% of primary AML samples present with hypermethylated BRCA1 (Scardocci et al 2006). Although this finding has not been confirmed in other studies (Bianco et al 2000, Esteller et al 2001, a meta-analysis performed in 2007 which reviewed risks for hematological malignancies associated with mutations in BRCA1/2 pathway, showed that defects in this pathway increase the risk for a subset of AML that are related to gene rearrangements (Friedenson 2007).…”
Section: Dna Repair Deficiency Related To Hematological Malignanciesmentioning
confidence: 79%
“…Apart from the above polymorphisms, several studies implicate BRCA1 (involved in initial recognition of a double strand break) and BRCA2 gene (involved in Homologous Recombination) deficiencies in AML pathogenesis. Scardocci et al observed that 32% of primary AML samples present with hypermethylated BRCA1 (Scardocci et al 2006). Although this finding has not been confirmed in other studies (Bianco et al 2000, Esteller et al 2001, a meta-analysis performed in 2007 which reviewed risks for hematological malignancies associated with mutations in BRCA1/2 pathway, showed that defects in this pathway increase the risk for a subset of AML that are related to gene rearrangements (Friedenson 2007).…”
Section: Dna Repair Deficiency Related To Hematological Malignanciesmentioning
confidence: 79%
“…However, important lessons may be learnt from studying the affected genes in the above syndromes and from other highly penetrant cancer conditions because it is possible that genetic variants in these pathways would predispose to t-AML. One such recent example is a study by Scardocci et al (2006) which demonstrated reduced BRCA1 expression due to promoter hypermethylation in t-AML. The hypermethylation was not seen in the majority of the primary tumours studied suggestive of a role of the cytotoxic therapy in the induction of DNA hypermethylation in t-AML.…”
Section: Genetic Mutations Predisposing To T-amlmentioning
confidence: 99%
“…The hypermethylation was not seen in the majority of the primary tumours studied suggestive of a role of the cytotoxic therapy in the induction of DNA hypermethylation in t-AML. Intererestingly, AML samples with BRCA1 hypermethlation had a higher level of karyotypic abnormalities indicative of the important role of BRCA1 in DNA damage repair (Scardocci et al, 2006). Polymorphisms exist in a number of genes involved in these cancer-pathways (e.g.…”
Section: Genetic Mutations Predisposing To T-amlmentioning
confidence: 99%
“…Fanconi anemia (FA) is transmitted as an autosomal recessive inheritance disease with direct linkage on chromosome X characterized by multiple congenital defects, failure of bone marrow and increased risk of cancer. De novo mutations of the BRCA1 gene is closely associated with the occurrence of Acute myelogenic leukemia (AML) such as 32% of primary AML tumors and 75% of secondary AML tumors characterized by reduced expression of the BRCA1 gene [38]. Alongside BRCA2 mutations detected also in cases of nonHodgkin's lymphomas (NHL) [38].…”
Section: Fanconi Anemia and Mutations In Brca1 And 2 Genesmentioning
confidence: 99%
“…De novo mutations of the BRCA1 gene is closely associated with the occurrence of Acute myelogenic leukemia (AML) such as 32% of primary AML tumors and 75% of secondary AML tumors characterized by reduced expression of the BRCA1 gene [38]. Alongside BRCA2 mutations detected also in cases of nonHodgkin's lymphomas (NHL) [38]. The protein products of the BRCA1 and BRCA2 genes interact with the protein of Fanconi anemia forming a powerful functional complex.…”
Section: Fanconi Anemia and Mutations In Brca1 And 2 Genesmentioning
confidence: 99%